Comparing Outcomes of Telerehabilitation vs. In-Person Therapy in Knee Osteoarthritis Management - Tank, Arvind; Baldha, Garish; Ramchandran, Arunachalam; Dave, Vaibhav; Oza, Prachi (Journal of Neonatal Surgery, 2025)
Background: This study aimed to assess the effectiveness of telerehabilitation and in-person therapy in treating osteoarthritis (OA) of the knee in terms of pain management, functional improvement, and patient satisfaction. Method: A randomized controlled trial involved 120 participants with OA knee. Participants were randomly assigned to one of two groups: telerehabilitation (n = 60) or in-person therapy (n = 60). Both groups received a 12-week intervention program. The outcome measures were a patient satisfaction survey, the Western Ontario and McMaster Universities Osteoarthritis Index (WOMAC), and the Visual Analog Scale (VAS) for pain. Assessments were conducted at baseline, six weeks, and twelve weeks. Result: The WOMAC scores and VAS pain ratings of both groups showed a substantial improvement from baseline at 6 and 12 weeks (p<0.001). At 12 weeks, the groups' WOMAC scores (p=0.78) and VAS pain ratings (p=0.63) did not differ statistically significantly. Patient satisfaction did not significantly differ between the two groups (p=0.52). Conclusion: This study concluded that there was significant improvement in stretching exercise than the calcaneal taping For patients with limited access to traditional rehabilitation facilities, telerehabilitation appears to be an effective alternative to in-person therapy for the treatment of knee OA.